The Role of Nurses in Reducing Fear for Pediatric Patients with Intravenous Catheterization - Sapprasert, Krongkaew; Wannachot, Jariyaphon; Doungchan, Noppawan (Journal of The Royal Thai Army Nurses, 2023)
A basic procedure with which pediatric patients must face when admitted to the hospital is peripheral venous cannulation up to 95 percent. Intravenous catheterization is a procedure used for diagnose and treatment such as drug injection and Infusion Therapy. Pediatric patients view peripheral venous cannulation as a threatening situation because of pain from tissue destruction. This painful situation is a main factor causing fears among those patients and unsuccessful treatment. Nurse is a health professional closest to pediatric patients and plays an important role in the successful insertion of an intravascular catheter. Nurses not only have those skills and be expertise but also need to know their roles and the ways to help pediatric patients reduce their fear of intravenous catheterization. This academic paper aims to prevent abnormal fears regarding the development in pediatric patients, lessen the risk of delayed catheterization and raise nurses’ awareness about nursing activities in order to reduce fear of intravenous catheter insertion among pediatric patients.